Pengembangan Majalah Digital Berbasis Pendekatan Kontekstual Menggunakan Aplikasi Canva Pada Materi Getaran, Gelombang dan Bunyi - Mustari, Mukarramah; dwi wahyuni, yuliana; Yuberti, Yuberti (Papanda, 2024)
This research aims to develop digital magazine media based on a contextual approach using the Canva application on vibration, wave and sound material. This research and development uses the Borg and Gall development model proposed by Sugiyono. The subjects in this research were class VIII SMP/MTs students. This research data was obtained from the results of student and educator response questionnaires, validation questionnaires of material experts and media experts. The results of this research are; 1) digital magazine learning media has been developed based on a contextual approach using the Canva application on vibration, wave and sound material, 2) based on assessments from media experts, they get an average score percentage of 82%, material experts get an average score percentage of 81%. All results of the questionnaire recapitulation at the product validation stage received very feasible criteria; 3) the assessment results of SMP/MTs educators received a percentage of 91% and student responses received a percentage of 87% in the very interesting category. Based on assessments by material experts, media experts, responses from educators and students, it can be concluded that the digital magazine learning media based on a contextual approach using the Canva application on vibrations, waves and sounds is suitable and interesting to use as a learning media. Penelitian ini bertujuan mengembangkan media majalah digital berbasis pendekatan kontekstual menggunakan aplikasi canva pada materi getaran, gelombang dan bunyi. Penelitian dan pengembangan ini menggunakan model pengembangan dari Borg and Gall yang dikemukakan oleh Sugiyono. Subjek dalam penelitian ini adalah peserta didik SMP/MTs kelas VIII. Data penelitian ini diperoleh dari hasil angket respon peserta didik dan pendidik, angket validasi ahli materi dan ahli media. Hasil penelitian ini adalah; 1) telah dikembangkan media pembelajaran majalah digital berbasis pendekatan kontekstual menggunakan aplikasi canva pada materi getaran, gelombang dan bunyi, 2) berdasarkan penilaian dari para ahli media mendapatkan persentase skor rata-rata 82%, ahli materi mendapatkan persentase skor rata-rata 81%. Seluruh hasil rekapitulasi angket pada tahap validasi produk mendapatkan kriteria sangat layak; 3) hasil penilaian pendidik SMP/MTs mendapatkan presentase 91% dan respon peserta didik mendapatkan presentase 87% dalam kategori sangat menarik. Berdasarkan penilaian oleh ahli materi, ahli media, respon pendidik dan peserta didik maka dapat disimpulkan bahwa media pembelajaran majalah digital berbasis pendekatan kontekstual menggunakan aplikasi canva pada materi getaran, gelombang dan bunyi layak dan menarik digunakan sebagai media pembelajaran.